Systematization of the communitarian project Children victims of forced displacement at the organization leaving footprints of peace of the city of Cali - Ortiz-Salinas, Claudia Belarmina; Naranjo-Tamayo, Diana Catalina (Prospectiva. Revista de Trabajo Social e Intervención Social, 2009)
This document presents the re flections generated during the process of intervention-research with children who are victims of forced displacement and belong to the organization “Leaving footprints of peace” of the city of Cali. It begins by contextualizing the experience and by establishing the thematic units, such as the notion of subject and the paradigm from which the intervention is approached. Then the article concentrates on the findings and on the analytic framework used for the systematization of the experience. Finally, it presents some conclusions about the work done with this population.